Discordance Between Clinical Status and Chest X-Ray (CXR) in COVID-19 Patient with Asymptomatic Transmission in Jakarta - Erlina Burhan; Heidy Agustin; Agus Dwi Susanto; Ibrahim Nur Insan Putra Dharmawan; Markus Meyer; Rita Rogayah (Acta Medica Indonesiana)
Coronavirus Disease 2019 (COVID-19) symptoms are highly various in each patient. CXR are routinely used to monitor the disease progression. However, it is not known whether chest X-Ray (CXR) is a good modality to assess COVID-19 pneumonia.